Synthesis of novel heterostructured Fe-doped Cu2O/CuO/Cu nanocomposite: Enhanced sunlight driven photocatalytic activity, antibacterial and supercapacitor properties. Issue 23 (1st December 2022) - Uma, B.; Anantharaju, K.S.; Malini, S.; S. More, Sunil; Vidya, Y.S.; Meena, S.; Surendra, B.S.
Abstract: A novel, highly efficient, reusable heterostructured nanocomposite photocatalyst and antibacterial agent was prepared successfully by combustion method. The structural and crystallinity of synthesized nanocomposites were well characterized by Powder X-ray diffraction (P-XRD) which confirms the purity and phase formation by diffraction peaks related to CuO, Cu2 O, metallic Cu of nanocomposites. The proximity of Fe directly affects the crystallinity of Cu2 O/CuO/Cu (CCC) and changes the morphology with observable voids and pores in Scanning Electron Microscopy (SEM). In addition, X-Ray Photoelectron Spectroscopy (XPS) results indicated the existence of doped Fe as Fe 3+ and Fe 2+ ions within the CCC nanocomposite lattice. The UV–Visible absorption spectroscopy illustrates a decrease in the band gap energy for the nanocomposites CCC (1.9 eV) and CCC-Fe (1.7 eV) which proves the dopant Fe hinders the recombination of e - –h + pairs by trapping electrons and holes, causing an enhancement in this degradation process. This depicts the ability of Fe-doped CCC as a better photocatalyst under Sunlight irradiation than CCC. This was confirmed by the obtained results of photocatalytic performance of Fe doped CCC (5 mol%) on Methylene Blue (MB) and Rhodamine B (RhB) dyes. The degradation was found to be 93% and 81% respectively under irradiation of Sunlight for 60 min, whereas for CCC, the obtained result was 65% (MB) and 60% (RhB) under same condition. The CCC-Fe nanocomposite also shows considerable specific capacitance with 84.55 F/g from cyclic voltamogram and 83 F/g from charge discharge studies with durability of 2000 cycles ascertains the supercapacitor nature. Further, the remarkable antibacterial activities of Fe-doped CCC nanocomposites against E. coli and S. Aureus (100 μg/mL) were discussed. The excellent results of Fe-doped CCC nanocomposite showed a prominent multifunctionality in suppressing organic pollutants and bacteria in the environment.